Insights into the synergy between functional microbes and dissolved oxygen partition in the single-stage partial nitritation-anammox granules system. (March 2022) - Wang, Hong; Yang, Min; Liu, Ke; Yang, Enzhe; Chen, Jing; Wu, Sha; Xie, Min; Wang, Dongbo; Deng, Hengwei; Chen, Hong
Graphical abstract: Highlights: DO partition was obtained in a single-stage PNA system. A high TNRE of 82.6% was achieved, and the NRR reached 1.24 kg-N/m 3 /d. The synergy between different functional microbes was enhanced via DO partition. Sludge granulation enriched the functional microbes and promoted the synergy. Abstract: The rapid start-up and stable operation of the single-stage partial nitritation-anammox (PNA) process remains a challenge in practical applications. An integrated investigation of nitrogen removal performance, sludge characteristics, activity and abundance, and microbial dynamics was implemented for 360 days via an airlift internal circulation reactor. During long-term operation, the reactor realized a stable dissolved oxygen (DO) partition and cultivated granular sludge. The nitrogen removal rate increased from 0.15 kg-N/m 3 /d to 1.24 kg-N/m 3 /d, and a high nitrogen removal efficiency of 82.6% was obtained. A stable DO partition further accelerated the bioreaction rates and enhanced the activity of functional microbes. The activities of ammonia oxidation and anammox reached 1.21 g-N/g-VSS/d and 1.43 g-N/g-VSS/d, respectively. Sludge granulation efficiently enriched the abundances of Candidatus Brocadia (7.4%) and Nitrosomonas (5.2%). These results demonstrated that efficient DO partition and stable culture of granular sludge could enhance the synergy of functional microbes for autotrophic nitrogen removal.